Lipoleiomyoma: a case report - Mittal, Saurav; Shivde, Rajendra; Azhar, Shaikh; Krutik, Patel; Prasla, Shopnil (International Journal of Advances in Medicine, 2016)
Lipoleiomyomas are benign tumors of the uterus, with predominant fatty component. It is a variant of leiomyoma. Most commonly seen in peri-menopausal women and is hyperechoic on ultrasound examination. The lesion is mostly asymptomatic and requires no treatment.